Optimization and potential assessment of CO2 geological storage caprock in the saline aquifers of the Qingjiang Basin, middle and lower reaches of the Yangtze River - Yuchen Tian; Shiqi Liu; Sijian Zheng; Shuxun Sang; Yinghai Liu; Shiheng Chen; Helong Zhang; Yanzhi Liu; Yuntian Jiang; Zekun Yue; Wenkai Wang (Unconventional Resources)
CO2 geological storage is seen as a key technology for reaching carbon neutrality. The Qingjiang Basin, located in Jiangxi, China, is experiencing rapid industrialization and urbanization leading to increased natural resource and energy consumption. The basin is located in the middle and lower reaches of the Yangtze River. A study was conducted in response to the geological characteristics of the Qingjiang Basin to optimize caprock for CO2 geological storage in saline aquifers and assess its potential. The research initially outlined the regional geological background of the Qingjiang Basin, including its tectonic position, stratigraphic distribution, sedimentary features, and the division of secondary structural units. By combining the regional geological conditions, the study analyzed the basin's formation and evolution history, sedimentary characteristics, reservoir and caprock development features, and geothermal geological conditions. This analysis provided critical geological factor evaluations for CO2 storage. Employing the calculation method proposed by the Carbon Sequestration Leadership Forum (CSLF), the study estimated the CO2 storage capacity in the deep saline aquifers of the Qingjiang Basin. The study revealed a total storage potential of 6.76 × 108 tons, with the central depression zone having the greatest potential, accounting for over 90 % of the total. Based on these findings, a hierarchical structure model was constructed, including three evaluation index layers and 21 evaluation indicators. A fuzzy comprehensive evaluation method combining the analytic hierarchy process and weighted judgment method was used to assess the suitability of CO2 geological storage in the Qingjiang Basin. The evaluation results indicated that the central depression zone had the highest comprehensive score and the best suitability for storage, making it the most favorable area for CO2 storage in the Qingjiang Basin. The research outcomes can provide theoretical support for advancing the study of CO2 saline aquifer storage in the lower reaches of the Yangtze River region in China.